CLINICAL EFFECTIVENESS OF EARLY ACUTE MYOCARDIAL INFARCTION DIAGNOSTICS, BASED ON THE ASSESSMENT OF CARDIAC FATTY ACID BINDING PROTEIN LEVELS - A. I. Martynov; M. I. Voevoda; G. P. Arutyunov; V. A. Kokorin; A. A. Spasskyi (Российский кардиологический журнал, 2012)
Aim. To investigate the diagnostic potential of cardiac fatty acid binding protein (cFABP) vs. cardiac troponins at the early stages of acute coronary syndrome (ACS), by comparing specificity and sensitivity of the qualitative assessment of their blood levels. Material and methods. The independent Russian multi-centre study ISPOLIN (Clinical effectiveness of early acute myocardial infarction diagnostics, based on the assessment of cFABP levels) included 1049 patients, who were hospitalised with possible ACS diagnosis, within 1–12 hours from the clinical onset. At admission, all participants underwent a qualitative assessment of cFABP and troponin I (TrI) blood levels. For each test, sensitivity, specificity, accuracy, positive predictive value (PPV) and negative predictive value (NPV) were examined for the whole sample, as well as by gender, age, body mass index (BMI), test time, and electrocardiographic (ECG) changes. Results. The sensitivity of cFABP test was higher than that for TrI (73,8% vs. 46,7%, respectively). Specificity reached 92% and 97,2%, respectively. Respective accuracy values were 79,3% and 62,2%. PPV was 0,95 for cFABP and 0,97 for TrI, while NPV was 0,61 and 0,45, respectively. The maximal sensitivity of cFABP test was observed within 3–6 hours from the onset of acute myocardial infarction, and exceeded the sensitivity of TrI test by 18–32% at all examined time points. Regardless of the ECG change type, sensitivity of cFABP test was higher than that of TrI test by 19–73%. For both tests, sensitivity and specificity did not correlate with age, gender, or BMI. Conclusion. Within the first 12 hours from the clinical onset of possible ACS, a Russian express test, which qualitatively assesses cFABP levels, demonstrated higher sensitivity, accuracy, and NPV, compared to the TrI test. The cFABP test can, therefore, be recommended for a wider use in clinical practice.